Clinical features of autoimmune cerebellar ataxia related to neuronal antibodies - Cai, Yun; Hua, Zhijuan; Chen, Yanan; Chen, Xue; Liu, Na; Liu, Ting; Zhou, Qianwen; Li, Jinghua; Di, Weiying (Frontiers in Immunology, 2025)
ObjectiveThis study aimed to investigate the clinical features of neuronal antibodies related to autoimmune cerebellar ataxia (ACA) and to provide guidance for the diagnosis and treatment of this disease.MethodsDemographic and clinical data were collected from antibody-positive patients with ACA who were admitted to the Department of Neurology, Affiliated Hospital of Hebei University, from January 2018 to February 2023. A retrospective analysis on the clinical manifestations, laboratory examinations, imaging data, treatment, and prognosis was performed.ResultsA total of six patients, including one man and five women, with a median age of 52.5 years, were enrolled in this study. All patients presented with dizziness and gait abnormalities with or without dysarthria. No tumor was found in these patients. Three patients were at the prodromal stage of infection, while one patient exhibited post-ACA fever symptoms and aggravated disease phenotypes. Three patients were positive for anti-glutamate decarboxylase (GAD), while one patient was positive for each of the anti-Tr, anti-mGluR1, and anti-Homer-3 antibodies. The white blood cell (WBC) count and the protein levels of the cerebrospinal fluid (CSF) were increased in four patients, which was in agreement with predominant lymphocytic inflammation. One patient displayed positive signals for CSF-specific oligoclonal proteins. Of the six patients, two were diagnosed with bilateral cerebellar atrophy, and two patients had nonspecific white matter changes. All of the patients received immunotherapy and rehabilitation treatment. Except for the Homer-3-positive patient, the remaining patients showed good prognosis. One patient relapsed.ConclusionACA can be induced or aggravated by infection. The detection of neuronal antibodies is crucial for the precise diagnosis of ACA. Cerebellar system symptoms, such as dizziness, unsteady walking, nystagmus, and dysarthria, are the first and main manifestations of ACA. The head magnetic resonance imaging (MRI) in patients with ACA may be normal or may exhibit abnormalities including cerebellar atrophy and nonspecific white matter changes. Immunotherapy could be effective in most patients with ACA.